Islamic Bank and Green Economy: A Systematic Literature Review - Mahmud Yusuf (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2025)
This study aims to map the existing literature, provide a comprehensive overview, and propose future research directions on the topic of Islamic banking and the green economy. The study employs a Systematic Literature Review (SLR) approach. Data were initially collected from the Scopus database using the Publish or Perish software, followed by journal quality assessment using the SCImago Journal & Country Rank (SJR) website. Both processes were documented using the PRISMA Flow Diagram. Subsequently, bibliometric mapping was conducted using VOSviewer, followed by a narrative synthesis and the formulation of future research suggestions related to Islamic banking and the green economy. The findings reveal that at least 37 Scopus-indexed journal articles have discussed the relationship between Islamic banking and the green economy, with the majority published in Quartile 2 (Q2) and Quartile 3 (Q3) journals. Scholarly attention to this topic began to increase significantly in 2019 and peaked in 2023. Taslima Julia emerged as the most prolific first author, having published four articles, while Emerald Publishing was identified as the most active publisher, with twelve publications. Broadly, the literature can be classified into five major clusters: (1) theoretical perspectives, (2) development and determinant factors, (3) green banking practices and their impact, (4) reporting, disclosure, and measurement, and (5) comparative studies. Furthermore, this study proposes four promising future research directions that remain underexplored and warrant further investigation. This study has several limitations. First, the analysis is limited to journal articles indexed in the Scopus database. Second, the review covers publications within the period of 2013–2023 only. In addition, the proposed future research agenda remains relatively limited. To the best of our knowledge, no previous systematic literature review has specifically examined the intersection between Islamic banking and the green economy in the manner presented in this study.